Effect of IAA and GA3 toward the growing and saponin content of purwaceng (Pimpinella alpina) - DASIYEM FATHONAH; SUGIYARTO SUGIYARTO (Nusantara Bioscience, 2009)
Abstract. Fathonah D, Sugiyarto. 2009. Effect of IAA and GA3 toward the growing and saponin content of purwaceng (Pimpinella alpina). Nusantara Bioscience 1: 17-22. The aims of this research are to examine (i) the effect of IAA and GA3 in different concentrations on the growth of the plants and (ii) the saponin contained inside the P. alpina leaves. The research was done in Sikunang Village, Kejajar Subdistrict, Wonosobo District, Central Java, from July to November 2007. The Completely Random Design used the experimental methods with two factors to analyze this experiment. The first treatment gives IAA and GA3; the second provides different IAA and GA3 concentrations. These experiments were repeated three times. Variables measured in this research were plant growth consisting of the number of leaves, their height, width, wet weight, and dry weight. The chemical compound of the secondary metabolite in the form of leave saponin was employed. Analysis of Variance (ANOVA) analyzed the result, then continued to Duncan Multiple Range Test in 5% level to analyze the real difference between those treatments. The result showed that giving IAA and GA3 differently affects the growth of P. alpina. In variable of the height, the optimal wet weight and dry weight in GA3 treatment was 50 ppm; an optimum number of leaves in GA3 treatment was 50 ppm, whereas the leaves width in IAA treatment was 200 ppm and GA3 treatment was 75 ppm. Optimum saponin treatment was IAA 200 ppm and GA3 25 ppm.